PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBANTUAN MEDIA GEOGEBRA TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS XI SMAN 1 KECAMATAN GUGUAK - Yona, Aiga Dwi (Departemen Matematika, 2024)
Students are expected to have problem solving skills in mathematics as one of the learning objectives. Nonetheless, this is a problem for SMA Negeri 1 Guguak District class XI students. It can be seen from the students' first test scores which, according to the indicators, did not reach good grades. Among the approaches utilised to overcome this problem is Problem Based Learning (PBL). This research seeks to find out whether SMA Negeri 1 Kecamatan Guguak grade XI students who use this approach along with Geogebra media can outperform their peers in traditional maths classes and without technology. This study used a quasi-experimental design with an unequal control group and posttest only. Students of class XI G SOS 1 and XI G SOS 2 of SMA Negeri 1 Guguak District were the subjects in this study. A mathematical problem solving ability test using open-ended questions was used as the research technique. We obtained a p-value of 0.005 after conducting a t-test on the data. If the p-value is smaller than α = 0.05, then the null hypothesis (H0) is rejected. This allows us to draw a conclusion. Therefore, it can be said that compared to traditional/conventional learning, SMA Negeri 1 Guguak class XI students who were applied the PBL paradigm assisted by Geogebra had better performance in solving mathematics problems.